2010
DOI: 10.1093/aobpla/plq010
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and physiological responses of lowland purple nutsedge (Cyperus rotundus L.) to flooding

Abstract: Comparing a lowland and an upland ecotype of Cyperus rotundus, the former had greater carbohydrate reserves in tubers, thicker roots and stems with larger air spaces and, under hypoxia, it maintained relatively lower activities of alcohol dehydrogenase and lactate dehydrogenase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…Increases in PDC and ADH activities have been associated with tolerance in various species. Valdez (1995) and Ismail et al (2009) reported higher PDC and ADH activities in tolerant rice genotypes when compared with sensitive ones; Peña-Fronteras et al (2009) and Fuentes et al (2010) showed similar results in flood-tolerant lowland ecotypes of C. rotundus; and this was also reported in other plants such as maize ( Schwartz 1969 ) and A. thaliana ( Dolferus et al 2003 ).…”
Section: Discussionmentioning
confidence: 62%
“…Increases in PDC and ADH activities have been associated with tolerance in various species. Valdez (1995) and Ismail et al (2009) reported higher PDC and ADH activities in tolerant rice genotypes when compared with sensitive ones; Peña-Fronteras et al (2009) and Fuentes et al (2010) showed similar results in flood-tolerant lowland ecotypes of C. rotundus; and this was also reported in other plants such as maize ( Schwartz 1969 ) and A. thaliana ( Dolferus et al 2003 ).…”
Section: Discussionmentioning
confidence: 62%
“…Fish farming can thus serve as an excellent model system to study how specific selection pressures have led to phenotypic differentiation. Adaptation to anthropogenic environments has also been suggested for C. rotundus , where the recently evolved lowland ecotype is thought to have acquired numerous adaptive traits under the selection pressure of repeated management practices in flooded rice fields in the Philippines (Fuentes et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In the genus Cyperus , only the perennial C. rotundus , a major weed of crops and vegetables, has been investigated for its response to flooding so far (Fuentes et al, 2010). Along with larger air spaces in the culms and larger tubers with higher carbohydrate content, a steady activity of alcohol dehydrogenase in the roots as a measure of sustained anaerobic respiration under hypoxia characterizes the flood-tolerant ecotype of C. rotundus .…”
Section: Discussionmentioning
confidence: 99%
“…The absorption at 620 nm of the sample was measured using ultra-violet spectrophotometer with glucose as standard. The starch concentration was determined by enzymatic hydrolysis following the method of Fuentes et al (2010). The residue that was obtained after the analysis of soluble sugars was oven-dried at 70°C overnight.…”
Section: Plant Physiological Parameters and Mycorrhizal Colonization mentioning
confidence: 99%